1996
DOI: 10.1021/bi952204b
|View full text |Cite
|
Sign up to set email alerts
|

Role of Portal Region Lysine Residues in Electrostatic Interactions between Heart Fatty Acid Binding Protein and Phospholipid Membranes

Abstract: The structure of heart fatty acid binding protein (HFABP) is a flattened beta-barrel comprising 10 antiparallel beta-sheets capped by two alpha-helical segments. The helical cap region is hypothesized to behave as a portal "lid" for the entry and release of ligand from the binding pocket. The transfer of fatty acid from HFABP is thought to occur via effective collisional interactions with membranes, and these interactions are enhanced when transfer is to membranes of net negative charge, thus implying that spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
137
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(145 citation statements)
references
References 32 publications
7
137
1
Order By: Relevance
“…We have also demonstrated that cationic residues on IFABP's surface play a primary role in establishing electrostatic interactions with phospholipid membranes [32], and the same has been observed for other members of the family that present a collisinal mechanism [36]. "Collisional FABPs" show a very similar surface electrostatic potential topology, they have a net positive potential in the α-helical region supporting the importance of this region in the interaction with membranes [37].…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…We have also demonstrated that cationic residues on IFABP's surface play a primary role in establishing electrostatic interactions with phospholipid membranes [32], and the same has been observed for other members of the family that present a collisinal mechanism [36]. "Collisional FABPs" show a very similar surface electrostatic potential topology, they have a net positive potential in the α-helical region supporting the importance of this region in the interaction with membranes [37].…”
Section: Discussionsupporting
confidence: 53%
“…On the other hand it has also been shown that IFABP transfers the ligand via a collisional FA transfer mechanism, where a proteinmembrane complex is formed [9]. This collisional FA transfer mechanism has also been observed with other members of the FABP family, including H-, A, and KFABP [34][35][36].…”
Section: Discussionmentioning
confidence: 95%
“…Heart and adipose FABPs both transfer FABPs at a ' fast ' rate relative to liver FABP and both transfer fatty acids via similar collisional mechanisms [25,26], but the rate of fatty acid transfer is affected by pH, ionic strength, phospholipid head-group charge on acceptor membranes and surface charge on donating FABPs [25,26,28,30]. Accordingly, Herr et al [30] proposed that FABPs may target fatty acid delivery to different intracellular compartments based on variation in organelle membrane lipid composition.…”
Section: Figure 6 Differences Between Primary Structure Of Teleost H mentioning
confidence: 99%
“…In particular, certain lysine residues within ␣-helix I of heart (8) and adipose (9) FABP, which are amphipathic helices, are implicated in the process. Moreover, in the case of intestinal FABP, a helix-less mutant was unable to participate in a collisional transfer mechanism (10,11).…”
mentioning
confidence: 99%